Public Trust and Attitude towards Green Marketing Strategies in Northern Kerala - Dr. V. Vijayakumar; Dr. P. K. Retheesh; N.Karunakaran (Journal of Advanced Research in Operational and Marketing Management, 2026)
This research explores the trust and attitudes of consumers towards green marketing strategies implemented by companies in Northern Kerala, specifically focusing on the districts of Kasaragod, Kannur, Wayanad, and Kozhikode. Green marketing refers to the promotion of environmentally friendly products and services and has gained increased relevance in the context of rising global awareness about sustainability and ecological conservation. The core objective of the study is to assess public perception of green marketing initiatives, evaluate their level of awareness about green products, analyse consumer purchasing behaviour, and examine their willingness to pay a premium for such products. To achieve these objectives, primary data was collected from 200 respondents through a structured questionnaire comprising both closed and open-ended questions. The sample was carefully designed to include diverse age groups, educational levels, occupations, and a balanced mix of urban and rural populations across the selected districts. Additionally, secondary data from academic journals, articles, and online resources was used to support the analysis. The findings indicate that while approximately 78% of respondents were aware of green marketing, only 64% had actually purchased green products, and among them, just 41% reported high satisfaction. Price sensitivity emerged as a significant deterrent, with 52% of non-buyers citing high prices as a reason for avoiding green products. Although 49% of respondents expressed willingness to pay more, their motivation was driven more by concerns for environmental protection and personal well-being than by brand loyalty. The study concludes that while there is a fair level of awareness and a generally favourable attitude towards green marketing in Northern Kerala, consumer trust remains tentative due to scepticism about companies’ green claims and the premium pricing of such products. Limited product knowledge and inadequate communication about the long-term benefits of green alternatives further restrict consumer participation. The paper recommends that companies invest in transparent marketing practices and educational campaigns to build credibility. Moreover, policy interventions such as subsidies or tax incentives could help make green products more affordable and accessible. A joint effort from businesses, government bodies, and civil society is essential to foster a strong green marketing ecosystem and encourage sustainable consumer behaviour across the region.